2021
DOI: 10.1038/s41598-021-98028-2
|View full text |Cite
|
Sign up to set email alerts
|

Customer demand-driven low-carbon vehicles combined strategy and route optimisation integrated decision

Abstract: With the optimal operating cost and optimal carbon emission target of the chemical logistics companies, a low-carbon routing optimisation with a multi-energy type vehicle combined problem is proposed by considering the concept of the logistics companies’ low-carbon behaviour. An integrated decision-making of multi-energy type vehicles combined strategy and route optimisation based on customer demand is presented, and an improved genetic algorithm is designed. A case study is then applied based on the data coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Research over the past decades has shown that demand function modelling is very useful for understanding customer demand in commodity economies [54][55][56][57][58]. Te demand function model can also be used as a way to establish the existence and uniqueness of the optimal solution for proft maximization of diferent products and can be efective in representing some of the properties of the optimal solution to fnd the optimal ordering strategy for the problem under consideration to achieve the best possible equilibrium between uncertain supply and demand.…”
Section: Nonessential Demand Functionmentioning
confidence: 99%
“…Research over the past decades has shown that demand function modelling is very useful for understanding customer demand in commodity economies [54][55][56][57][58]. Te demand function model can also be used as a way to establish the existence and uniqueness of the optimal solution for proft maximization of diferent products and can be efective in representing some of the properties of the optimal solution to fnd the optimal ordering strategy for the problem under consideration to achieve the best possible equilibrium between uncertain supply and demand.…”
Section: Nonessential Demand Functionmentioning
confidence: 99%
“…Customer demand is complex, and different people, backgrounds, economic strengths, social experiences, and cultures produce different customer needs. Research over the last few decades has shown that demand function modelling can be of great help in understanding customer demand in a commodity economy [33][34][35][36][37]. The demand function can be used as a way to…”
Section: Variable Functionsmentioning
confidence: 99%
“…These environmental efforts have the potential to cut the environmental impact and in some cases they can lead to other benefitsfor example, the financial gains from using route optimisation (Liu et al, 2021). However, their use requires the development of resources and competences.…”
Section: Green Logistics and The Road Freight Transportmentioning
confidence: 99%